On Asymptotically \(f\)-statistical Equivalent Set Sequences in the Sense of Wijsman - Konca, Åžükran; Küçükaslan, Mehmet (Communications in Mathematics and Applications, 2019)
The aim of this paper is to introduce a generalization of statistical convergence of asymptotically equivalent set sequences and examine some inclusion relations related to a new concept of Wijsman asymptotically equivalent statistical convergence of sequences of sets with respect to a modulus function \(f\).
Keywords: Statistical convergence; Sequence space; Modulus function; Asymptotically equivalent set sequences; Wijsman convergence